Biochemical studies on the protective effect of honey against doxorubicin-induced toxicity in BALB/C mice - Alhumaydhi, Fahad A. (International Journal of Health Sciences, 2020)
Objective: Doxorubicin-mediated chemotherapy has been linked in cancer patients with acute toxic manifestations. This study aimed to assess the protective effect of natural honey against doxorubicin-induced toxicity in mice. Methods: Forty male BALB/C mice were divided randomly and equally into four groups of ten mice. Group I was on a normal diet and served as the control. Group II received only honey to investigate its antitoxic effects (oral administration at 10 g/kg for 10 days). Group III was injected with a single dose of doxorubicin (10 mg/kg i.p.). Group IV received both doxorubicin and honey. On day 11, blood was taken from the various groups of mice and the quantitative and qualitative changes were observed in the white blood cells. The levels of hepatic, renal, and cardiac toxicity biomarkers including aspartate aminotransaminase (AST), alanine minotransaminase (ALT), blood nitrogen urea (BUN), serum creatinine, lactate dehydrogenase (LDH), and creatinine kinase (CK) were also assessed. Results: This study revealed that doxorubicin caused acute toxicity, including weight loss, depletion of white blood cells, and altered liver, kidney, and cardiac parameters (P < 0.05). White blood cells in the blood picture from the doxorubicin-injected mice exhibited toxicological changes, including abnormal morphology, disorganized nuclei, dispersed chromatin strands, and granules. The consumption of honey improved the liver, kidney, and heart biomarkers of toxicity in doxorubicin-injected mice (P < 0.05). Honey reduced the levels of ALT, AST, BUN, serum creatinine, LDH, and CK in doxorubicin-injected mice (P < 0.05). Conclusion: The findings suggest that the consumption of natural honey can alleviate doxorubicin-induced toxicity in cancer patients.